Identification of key ferroptosis-related genes and therapeutic target in nasopharyngeal carcinoma - Gu, Yuanyuan; Zhou, Yaozhuang; Xie, Chunhua; He, Guangyao; Zhang, Maosheng (Frontiers in Genetics, 2025)
ObjectiveNasopharyngeal carcinoma (NPC) is a malignant tumor, but the role of ferroptosis-related genes in NPC remains unclear. This study aimed to identify ferroptosis-related therapeutic targets and explore their mechanisms in NPC.MethodNPC datasets and ferroptosis-related genes were obtained from GEO and FerrDB, respectively. Ferroptosis-related differentially expressed genes (DEGs) were identified, and Weighted Gene Co-expression Network Analysis (WGCNA) was used to pinpoint disease-related genes. Four machine learning algorithms screened hub genes, validated by ROC curves. Functional enrichment (GSEA, GSVA), drug prediction (DGIdb), immune infiltration analysis (CIBERSORT), and single-cell RNA sequencing (scRNA-seq) were performed.ResultFrom 3405 DEGs, 90 ferroptosis-related genes were identified, enriched in ferroptosis, IL-17, and p53 signaling pathways. WGCNA revealed 34 disease-related genes, and four hub genes (TBK1, KIF20A, SLC16A1, QSOX1) were selected, showing high diagnostic efficacy. GSEA/GSVA highlighted pathway differences between high/low expression groups. Eleven potential drugs were predicted, and immune analysis indicated increased macrophage M1 and neutrophil infiltration. scRNA-seq validated hub gene expression profiles.ConclusionThis study identified four ferroptosis hub genes in NPC, offering insights into its molecular mechanisms and potential diagnostic/therapeutic targets.